2022
DOI: 10.1007/s13132-022-01086-8
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Components of Digital MSMEs Ecosystem for Inclusive Digital Economy in Indonesia

Abstract: The study examined the interactive components of digital micro and small medium enterprise (MSMEs) ecosystem for inclusive digital economy, more specifically found ways to put the digital MSMEs ecosystem to work for accelerating the MSMEs digitalization. The multiple cases studies' findings and discussion supported the model building. The model of digital MSMEs ecosystem was formulated as the surrounding interactive components of ecosystem, enabling digital MSMEs to realize and accelerate toward the digital ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
8

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 40 publications
0
8
0
8
Order By: Relevance
“…Innovation strategy as hypothesized shows that innovation strategy positively influences sustainable competitive advantage through innovation processes and systems. As an important part of implementing an innovation strategy, innovation processes and innovation systems are stated to be able to increase sustainable competitive advantage in MSMEs (Aminullah et al, 2022;Candraningrat et al, 2021;Gao et al, 2023). Research on innovation strategy shows that processes and systems have a significant impact and emphasizes the need for special efforts to implement innovation at a strategic level, especially with active efforts to update products and services to respond to diverse market needs (Kilay et al, 2022;Octasylva et al, 2022;Suharyati & Utami, 2022).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Innovation strategy as hypothesized shows that innovation strategy positively influences sustainable competitive advantage through innovation processes and systems. As an important part of implementing an innovation strategy, innovation processes and innovation systems are stated to be able to increase sustainable competitive advantage in MSMEs (Aminullah et al, 2022;Candraningrat et al, 2021;Gao et al, 2023). Research on innovation strategy shows that processes and systems have a significant impact and emphasizes the need for special efforts to implement innovation at a strategic level, especially with active efforts to update products and services to respond to diverse market needs (Kilay et al, 2022;Octasylva et al, 2022;Suharyati & Utami, 2022).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Shahbaz et al [10] investigated the effect of the digital economy on the structure of renewable energy consumption. Aminullah et al [11] examined the interactive components of the digital micro and small medium enterprise (MSMEs) ecosystem for an inclusive digital economy. Yu et al [12] adopted a multistage DID model to evaluate the impact of the digital economy on highquality economic development and found that the digital economy has a significant role in promoting high-quality economic development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An important effort that must be made to succeed in digitizing SMEs in a sustainable manner is to continue to develop the digital competencies of SMEs actors (Cassetta et al, 2020;North et al, 2019). Efforts to develop digital competence can be carried out by various parties, ranging from government officials, investors, to academics (Aminullah et al, 2022). In this research, a framework was developed to carry out digital competency development for SMEs actors, namely as follows.…”
Section: Development Of Digital Competence For Smes Actorsmentioning
confidence: 99%